Designing Sodium Manganese Oxide with 4 d‐Cation Zr Doping as a High‐Rate‐Performance Cathode for Sodium‐Ion Batteries. Issue 12 (19th May 2020) - Shi, Wen‐Jing; Zheng, Ya‐Min; Meng, Xiao‐Meng; Liu, Shi‐Bin; Xu, Shou‐Dong; Chen, Liang; Wang, Xiao‐Min; Zhang, Ding
Abstract: Invited for this month's cover picture is the group of Shi‐Bin Liu and Ding Zhang from Taiyuan University of Technology (China). The cover picture shows that the 4d‐cation Zr‐substitution shows high promotion on the electrochemical performance of tunnel‐type transition metal oxides as promising cathodes for sodium‐ion batteries. Read the full text of the Article at 10.1002/celc.202000205 . Abstract : "A Na 0.44 Mn 0.98 Zr 0.02 O2 cathode is designed by applying the cation‐substitution strategy. The effects of Zr doping on the structure and sodium storage performance are systematically investigated. The galvanostatic intermittent titration technique (GITT) and in situ XRD results indicate that Zr introduction significantly facilitates the Na + diffusion kinetics and decreases the volume change upon the electrode process, thus resulting in superior high‐rate performance and long cyclic stability…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.202000205 .